Variabilitas harian komunitas ikan padang lamun perairan Tanjung Tiram-Teluk Ambon Dalam [Daily variability of fish community in sea grass beds of Tanjung Tiram-Inner Ambon Bay] - Husain Latuconsina; Rohani Ambo- Rappe (Masyarakat Iktiologi Indonesia (Indonesian Ichthyological Society), 2013)
The research was conducted from July-August 2012 to examine day and night abundance and community structure of fish in seagrass area of Tanjung Tiram, Inner Ambon Bay. Fish were collected by swept area method using beach seine over the seagrass areas. Fish samples were collected six times (three times for each day and night). It was found that total number of individual fish as much as 5593 individuals from 72 species and 35 families. Siganus canaliculatus dominated the fish community structure at both day and night time. Ostorhinchus lateralis more active at night time, whereas Aeoliscus strigatus more active at day time. Fish community structure varied between day and night, index of dominancy was slightly higher at night, whereas index of diversity was higher during day time as well as the evenness index. Variability in abundance and community structure of fish between day and night were associated with nocturnal and diurnal fish charachetristic, and oceanographic parameters. Temperature, salinity, dissolved oxygen and pH were positively affected fish abundance; whereas the level of turbidity was negatively. Abstrak Penelitian ini dilaksanakan di perairan Tanjung Tiram , Teluk Ambon Dalam selama bulan Juli-Agustus 2012, untuk membandingkan kelimpahan dan struktur komunitas ikan padang lamun berdasarkan perbedaan siang dan malam hari. Ikan dikoleksi dengan metode sapuan menggunakan pukat pantai yang ditarik pada hamparan padang lamun sebanyak enam kali (masing-masing tiga kali mewakili siang dan malam hari). Hasil penelitian mendapatkan total jumlah individu ikan sebanyak 5593 individu dari 72 spesies dan 35 famili. Siganus canaliculatus mendominasi struktur komunitas ikan baik pada siang maupun malam hari, Ostorhinchus lateralis aktif pada malam hari, dan Aeoliscus strigatus yang aktif pada siang hari. Terdapat variasi struktur komunitas ikan antara siang dan malam, dengan nilai dominansi selalu lebih tinggi pada malam hari. Sebaliknya, keanekaragaman selalu tinggi pada siang hari dan keseragaman spesies lebih stabil pada siang hari. Variabilitas kelimpahan dan struktur komunitas ikan antara siang dan malam hari selain berkaitan dengan sifat nokturnal dan diurnal, juga dipengaruhi fluktuasi parameter oseanografi. Suhu, salinitas, oksigen terlarut, dan pH berpengaruh positif, sedangkan kekeruhan perairan berpengaruh negatif terhadap kelimpahan ikan di ekosistem padang lamun.